A biomechanical study on proximal junctional kyphosis following long-segment posterior spinal fusion - Zhu,Wen-Yi (2019)
Posterior long-segment spinal fusion may lead to proximal junctional kyphosis (PJK). The present study sought to identify the appropriate fusion levels required in order to prevent PJK using finite element analysis. A finite element model was constructed based on the whole-spine computed tomography findings of a healthy adult. Nine commonly used posterior spinal fusion methods were selected. Stress on the annulus fibrosis fibers, the posterior ligamentous complex, and the vertebrae after various spinal fusions in the upright position were compared. This study was divided into two groups: non-fusion and fusion. In the former, the stress between the T10 and the upper thoracic vertebrae was higher. Comparing thoracic and lumbar segments in the fusion group, the peak stress values of the upper instrumented vertebrae (UIV) were mainly observed in T2 and L2 whilst those of the UIV+1 were observed in T10 and L2. After normalization, the peak stress values of the UIV and UIV+1 were located in T2 and L2. Similarly, the peak stress values of the annulus fibrosus at the upper adjacent level were on T10 and L2 after normalization. However, the peak stress values of the interspinal/supraspinal complex forces were concentrated on T11, T12, and L1 after normalization whilst the peak stress value of the pedicle screw was on T2. Controversy remains over the fusion of T10, and this study simulated testing conditions with gravitational loading only. However, further assessment is needed prior to reaching definitive conclusions.